Tindak Tutur Direktif Guru Dalam Pembelajaran Bahasa Indonesia di Kelas VIII SMP Negeri 5 Sungai Beremas - Efitriani Andala Sari; Marni, Silvia; Sartika, Rina (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
Describe the form of directive speech acts of Indonesian teachers for class VIII in the teaching and learning process at SMP Negeri 5 Sungai Beremas. The type of research used in this research is a qualitative type. The method used in this research is descriptive method. The data in this study are in the form of directive speech acts of Indonesian teachers at SMP Negeri 5 Sungai Beremas in the teaching and learning process. The data source for this research is the speech of an Indonesian language teacher during the teaching and learning process from the beginning to the end of the lesson. research instruments used in research are recording devices such as; cellphone. For notes such as; pen, paper, or small notes, and other writing tools The data collection stage in this study used the listening or listening method. The data validation technique used in this study is a detailed description. The results of this study First, the form of directive speech acts used by teachers in learning at SMP Negeri 5 Sungai Beremas, there are five forms, namely, directive speech acts ordering, speech acts begging, directive speech acts suggesting, directive speech acts asking questions, directive speech acts prohibiting . Second, from the utterances that have been analyzed in SMP Negeri 5 Sungai Beremas the most dominant utterance or the most frequently used by the teacher in learning is the directive act of asking questions.